Effect of silver particles electrodeposited on reticulated vitreous carbon for nitrate reduction - Oishi, S. S.; Couto, A. B.; Botelho, E. C. [UNESP]; Ferreira, N. G. (The Electrochemical Society, 2017)
The electrocatalytic activity of silver particles electrodeposited on reticulated vitreous carbon (RVC) was evaluated for nitrate reduction. Different morphologies of silver deposits were obtained by varying the deposition potential, AgNO3 concentration solution, and deposition time. Silver deposit was not uniform due to the three-dimensional shaped electrode. The more elevated regions on the surface present a more intense deposition. The lowest silver ion concentration of 5 mM associated to the lowest deposition time of 10 s provided the most uniform Ag deposition. The electrocatalytic activities for nitrate reduction were improved for electrodes with Ag deposited at potential of -0.3 V, time of 60 s and silver ion concentrations of 10 and 20 mM, probably due to the connection between Ag dendrites and Ag nanoparticles that increased the electrode surface area.